2020
DOI: 10.3390/antiox9040320
|View full text |Cite
|
Sign up to set email alerts
|

Triple Combination of Ascorbate, Menadione and the Inhibition of Peroxiredoxin-1 Produces Synergistic Cytotoxic Effects in Triple-Negative Breast Cancer Cells

Abstract: Triple-negative breast cancer (TNBC) is an aggressive form of mammary malignancy currently without satisfactory systemic treatment options. Agents generating reactive oxygen species (ROS), such as ascorbate (Asc) and menadione (Men), especially applied in combination, have been proposed as an alternative anticancer modality. However, their effectiveness can be hampered by the cytoprotective effects of elevated antioxidant enzymes (e.g., peroxiredoxins, PRDX) in cancer. In this study, PRDX1 mRNA and protein exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
4
14
0
Order By: Relevance
“…Be that as it may, the insufficient number of clinical studies and some experimental flaws not addressed by them makes it difficult to ascertain whether antioxidants may be potential therapeutic adjuvants, which is the main topic of this review. In line with other authors [ 22 , 25 , 259 , 260 ] we highlight common breaches in clinical trials that challenge a successful translation of antioxidants into cancer management, such as: route of administration; difficulty to achieve maintained therapeutic concentrations; low patient number; lack of previous preclinical assessment of a safe, effective and clinically relevant dose regimen for a given antioxidant (as monotherapy and combined with other therapeutics such as chemotherapy, radiotherapy or immunotherapy) in appropriate models of the breast cancer subtype under investigation (preferably patient-derived xenografts and/or organoids); non-standardized readouts (such as the impact on patient’s “redoxidomics”, gene and/or protein expression, post-translational protein modifications at tumor and antioxidant defense levels, or even on immune system that includes tumor-infiltrating lymphocytes or tumor-associated macrophages) and patient stratification (adjuvant or neoadjuvant therapy, “redoxidomic” status, breast tumor subtype, nutritional state, bodyweight or healthy habits followed by case subjects); lack of information about the impact on clinical outcome (overall, relapse-and metastasis-free survival); and low multidisciplinary teams.…”
Section: Lessons From Clinical Trials: Achievements Challenges Ansupporting
confidence: 93%
See 1 more Smart Citation
“…Be that as it may, the insufficient number of clinical studies and some experimental flaws not addressed by them makes it difficult to ascertain whether antioxidants may be potential therapeutic adjuvants, which is the main topic of this review. In line with other authors [ 22 , 25 , 259 , 260 ] we highlight common breaches in clinical trials that challenge a successful translation of antioxidants into cancer management, such as: route of administration; difficulty to achieve maintained therapeutic concentrations; low patient number; lack of previous preclinical assessment of a safe, effective and clinically relevant dose regimen for a given antioxidant (as monotherapy and combined with other therapeutics such as chemotherapy, radiotherapy or immunotherapy) in appropriate models of the breast cancer subtype under investigation (preferably patient-derived xenografts and/or organoids); non-standardized readouts (such as the impact on patient’s “redoxidomics”, gene and/or protein expression, post-translational protein modifications at tumor and antioxidant defense levels, or even on immune system that includes tumor-infiltrating lymphocytes or tumor-associated macrophages) and patient stratification (adjuvant or neoadjuvant therapy, “redoxidomic” status, breast tumor subtype, nutritional state, bodyweight or healthy habits followed by case subjects); lack of information about the impact on clinical outcome (overall, relapse-and metastasis-free survival); and low multidisciplinary teams.…”
Section: Lessons From Clinical Trials: Achievements Challenges Ansupporting
confidence: 93%
“…Moreover, in TNBC, PRDX1 is crucial for maintaining the REDOX status and has a cytoprotective effect. Accordingly, PRDX1-knockdown resulted in the inhibition of cell growth in vitro and such effects were enhanced when it was combined with pro-oxidant agents like H 2 O 2 , glucose oxidase, sodium L-ascorbate or menadione [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, inhibiting the mTORC1 pathway via the AKT inhibitor, MK2206, or blocking the regulatory-associated protein of mTOR (RPTOR) with small interfering RNA (siRNA) potentiated gefitinib toxicity in TNBC cells [ 33 ]. Recently, more efficacious treatments for TNBC have been suggested that use a triple combination of drugs targeting multiple pathways simultaneously, such as redox homeostasis, DNA synthesis, DNA damage, histone deacetylase, and multiple protein kinases [ 35 , 36 , 37 ]. A drug combination discovery involving 33 FDA-approved PKIs revealed that the triple combination of dasatinib, afatinib (BIBW-2992), and trametinib (GSK1120212) was anti-proliferative in TNBC cells by inhibiting SRC, HER2/EGFR, and MEK [ 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression- and tumor-promoting effects of PRDX1 have been described in numerous types of human cancer 29 31 . Herein, our immunohistochemical staining results demonstrated that PRDX1 is also overexpressed in CRC tissues compared to ANTs (Fig.…”
Section: Resultsmentioning
confidence: 99%